PENGUATAN NILAI SOSIAL SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL - Alfia Usmi Latifah; Anindya Syifa Nuraini; Zidna Syifanadia IPM; Yona Wahyuningsih (STKIP Subang, 2025)
Social Studies (IPS) learning in elementary schools plays a strategic role in shaping students' social values, such as mutual cooperation, tolerance, empathy, and social responsibility. One approach that is considered effective in achieving these goals is the integration of local wisdom into IPS learning. This study aims to systematically examine how local wisdom-based IPS learning contributes to strengthening the social values of elementary school students. The method used was a Systematic Literature Review (SLR) with reference to the PRISMA guidelines. Articles were collected from national and international journals published between 2019 and 2025, focusing on social studies learning, local wisdom, and the social values of elementary school students. A total of 22 articles that met the inclusion criteria were analyzed and classified based on the study theme. The results of the study show that local wisdom-based social studies learning is consistently able to strengthen students' social values through the integration of cultural traditions, social practices, and contextual learning activities. Local wisdom serves as a concrete learning resource for internalizing the values of mutual cooperation, empathy, tolerance, and responsibility, which can develop students' social identity, social skills, and solidarity in the community. In addition, the findings also reveal implementation challenges, particularly related to teacher readiness, availability of teaching materials, and understanding of local culture. Overall, local wisdom-based social studies learning has proven to be relevant and effective as a pedagogical approach in strengthening the social values of elementary school students and supporting the development of contextual and sustainable social studies learning.